Bidirectional Association between First-Episode Panic Disorder and Major Depressive Disorder in a Nationwide General Population Survey in Korea - Woo, Jungmin; Hong, Jin Pyo; Cho, Seong-Jin; Lee, Jun-Young; Joen, Hong Jin; Kim, Byung-Soo; Chang, Sung Man (Journal of Korean medical science, 2019)
Panic disorder (PD) and major depressive disorder (MDD) can occur concurrently, despite different clinical manifestations. Because MDD and PD patients tend to have more complicated conditions, understanding the co-occurrence and pattern of these conditions is important. Here, we investigated the influence of PD and MDD on each other, with respect to time interval. Data from three national representative surveys were pooled (total 18,807 respondents), and the age of onset (AOO) of PD and MDD was analyzed. We performed Kaplan-Meier analysis to estimate separate survival functions, using the AOO of MDD and PD as the outcome. To understand the temporal effect of other disorders, we used a Cox proportional hazard model to estimate the hazard ratios for the onset of MDD/PD with other comorbidities as time-dependent covariates. PD elevated the risk of subsequent MDD by 1.5-fold, whereas MDD elevated the risk of subsequent PD by 3.8-fold. The effect of such an elevation risk was significant for up to 2 years. The results revealed a bidirectional relationship between MDD and PD. Each disease represents a risk of a subsequent occurrence of the other, which lasts for a considerable duration.